Origin of Light Noble Gases (He, Ne, and Ar) on Earth: A Review. (13th April 2018) - Péron, Sandrine; Moreira, Manuel; Agranier, Arnaud
Abstract: We review the different scenarios for the origin of light noble gases (He, Ne, and Ar) on Earth. Several sources could have contributed to the Earth's noble gas budget: implanted solar wind, solar nebula gas, chondrites, and comets. Although there is evidence for "solar‐like" neon in the Earth's mantle, questions remain as to its origin. A new compilation of noble gas data in lunar soils, interplanetary dust particles, micrometeorites, and solar wind allows examination of the implanted solar wind composition, which is key to understanding the "solar‐like" mantle neon isotope composition. We show that lunar soils that reflect this solar‐wind‐implanted signature have a 20 Ne/ 22 Ne ratio very close to that of ocean island basalts. New data and calculations illustrate that the measured plume source 20 Ne/ 22 Ne ratio is close to the primitive mantle ratio, when taking into account mixing with the upper mantle (that has lower 20 Ne/ 22 Ne ratio). This favors early solar wind implantation to account for the origin of light volatiles (He, Ne, and possibly H) in the Earth's mantle: they were incorporated by solar wind irradiation into the Earth's precursor grains during the first few Myr of the solar system's formation. These grains must have partially survived accretion processes (only a few percent are needed to satisfy the Earth's budget of light volatiles). As for the atmosphere, the neon isotope composition can be explained by mixing 36% of mantle gases having this solar‐wind‐implanted signature and 64% of chondritic gases delivered in a late veneer phase. Key Points: The neon isotopic ratios measured in oceanic island basalts are very close to the primitive mantle neon isotopic ratios The solar wind implantation on preplanetesimal dust can explain the origin of light volatiles (H, He, and Ne) in the Earth's mantle The atmospheric neon composition is accounted for by mixing 36% of mantle neon and 64% of neon from a chondritic or cometary source